Political economy analysis of sub-national health sector planning and budgeting: A case study of three counties in Kenya. - Benjamin Tsofa; Evelyn Waweru; Joshua Munywoki; Khaing Soe; Daniela C Rodriguez; Adam D Koon (Public Library of Science (PLoS), 2023)
Devolution represented a concerted attempt to bring decision making closer to service delivery in Kenya, including within the health sector. This transformation created county governments with independent executive (responsible for implementing) and legislative (responsible for agenda-setting) arms. These new arrangements have undergone several growing pains that complicate management practices, such as planning and budgeting. Relatively little is known, however, about how these functions have evolved and varied sub-nationally. We conducted a problem-driven political economy analysis to better understand how these planning and budgeting processes are structured, enacted, and subject to change, in three counties. Key informant interviews (n = 32) were conducted with purposively selected participants in Garissa, Kisumu, and Turkana Counties; and national level in 2021, with participants drawn from a wide range of stakeholders involved in health sector planning and budgeting. We found that while devolution has greatly expanded participation in sub-national health management, it has also complicated and politicized decision-making. In this way, county governments now have the authority to allocate resources based on the preferences of their constituents, but at the expense of efficiency. Moreover, budgets are often not aligned with priority-setting processes and are frequently undermined by disbursements delays from national treasury, inconsistent supply chains, and administrative capacity constraints. In conclusion, while devolution has greatly transformed sub-national health management in Kenya with longer-term potential for greater accountability and health equity, short-to-medium term challenges persist in developing efficient systems for engaging a diverse array of stakeholders in planning and budgeting processes. Redressing management capacity challenges between and within counties is essential to ensure that the Kenya health system is responsive to local communities and aligned with the progressive aspirations of its universal health coverage movement.